1999
DOI: 10.1063/1.873672
|View full text |Cite
|
Sign up to set email alerts
|

First experiments in the Dusty Plasma Experiment device

Abstract: The Dusty Plasma Experiment (DPX) is a new experimental plasma device at Fisk University. DPX is constructed from two, 4 in. diam ISO 100 stainless steel six-way crosses. Initial experiments have successfully produced argon dc glow discharge plasmas. Measurements of the plasma parameters using Langmuir probes, in the absence of the dust particles, give plasma densities n∼1015 m−3 and electron temperatures ranging from Te=2 to 5 eV. Dusty plasmas are made by suspending 40 μm diam silica (SiO2) particles in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(35 citation statements)
references
References 23 publications
1
34
0
Order By: Relevance
“…as well as experimentally (Chu et al 1994; Barkan et al 1995;Prabhakara and Tanna 1996;Thomas and Watson 1999;Pieper and Goree 1996) during the last few years. Rao et al (1990) have first reported theoretically the existence of extremely low phase velocity (in comparison with the electron and ion thermal velocities) dust-acoustic waves in an unmagnetized dusty plasma whose constituents are an inertial charged dust fluid and Boltzmann distributed ions and electrons.…”
mentioning
confidence: 97%
“…as well as experimentally (Chu et al 1994; Barkan et al 1995;Prabhakara and Tanna 1996;Thomas and Watson 1999;Pieper and Goree 1996) during the last few years. Rao et al (1990) have first reported theoretically the existence of extremely low phase velocity (in comparison with the electron and ion thermal velocities) dust-acoustic waves in an unmagnetized dusty plasma whose constituents are an inertial charged dust fluid and Boltzmann distributed ions and electrons.…”
mentioning
confidence: 97%
“…Finally, the author's group at Auburn University (US) has also made extensive use of the anodic dc glow discharge configuration. Early experiments made use of a biased anode and biased cathode for studies of microparticle charging [21] and the structural properties [29], [35], [37] of microparticle clouds. Recent experiments use a configuration similar to the Iowa DPD with a biased anode and grounded chamber as the cathode.…”
Section: Anodic Dischargementioning
confidence: 99%
“…In spite of these differences, dc-generated dusty plasmas have been shown to be an excellent platform for fundamental investigations of particle charging, [19], [20], [21], [22] a wide variety of collective effects including both dust-modified plasma waves [23], [24] and dust-driven waves, [25], [26], [27], [28], [29], [30], [31], [32] three-dimensional shaping effects, [33], [34], [35], [36], [37] and thermodynamic properties. [38], [39], [40], [41] The dc-generated dusty plasma enables a range of experimental studies that are distinct from, yet complementary with, studies in rf-generated dusty plasmas.…”
Section: Introductionmentioning
confidence: 99%
“…12 Upon charging, if a large negative sheath potential could be imposed at the dust surface, then the charged dust could be accelerated to energies equal to the sheath voltage multiplied by the total charge on the particle:…”
Section: Conceptual Description Of Dust Particle Accelerator Approachmentioning
confidence: 99%